Quantitative peptidomics using reductive methylation of amines - Dasgupta, Sayani; Castro, Leandro M. [UNESP]; Tashima, Alexandre K.; Fricker, Lloyd (Springer Nature, 2018)
A number of different approaches have been used for quantitative peptidomics. In this protocol we describe the method in which peptides are reacted with formaldehyde and sodium cyanoborohydride, which converts primary and secondary amines into tertiary amines. By using different combinations of regular reagents, deuterated reagents (2H), and reagents containing deuterium and 13C, it is possible to produce five isotopically distinct forms of the methylated peptides which can be quantified by mass spectrometry. Peptides with free N-termini that are primary amines incorporate two methyl groups using this procedure, which differ by 2 Da for each of the five isotopic combinations. Peptides that contain unmodified lysine residues incorporate additional pairs of methyl groups, leading to larger mass differences between isotopic forms. The reagents are commercially available, relatively inexpensive, and chemically stable.
Keywords: Cyanoborohydride; Formaldehyde; Isotopic labels